KUALITAS PELAYANAN FASILITAS KESEHATAN TINGKAT I NON PUSKESMAS DI KELURAHAN TANGKERANG TENGAH KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU TAHUN 2017 - Indah Dwi Puspasari; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study based on several problems found on health facilities service level 1 non Puskesmas at Tangkerang Tengah Marpoyan Damai Pekanbaru City, which are : (1) The doctors and midwifes are not work everyday (2) Lack of Human Resources (3) Lack of facilities such as, there is no ambulance at Arrabih Clinic. The formulation of problem in this study are (1) How the quality of health service level 1 non puskesmas at Tangkerang Tengah Marpoyan Damai Pekanbaru City (2) The factors that affect the quality of health facilities service level 1 Non Puskesmas at Tangkerang Tengah Kecamatan Marpoyan Damai Kota Pekanbaru 2017. The aims of this research are (1) To find out the quality of health facilities service level 1 non puskesmas at Tangkerang Tengah Marpoyan Damai Pekanbaru City Year 2017 (2) To find out the hamper factors that affect the health service at Tangkerang Tengah Kecamatan Marpoyan Damai Kota Pekanbaru 2017. The theory used is MENPAN Number 17 year 2017 about publiv service indicator: service procedure, service time, cost, service product, facilities and competency of the employee. This study is qualitative study with descriptive method. The result of this study shows that the quality of health service Tangkerang Tengah Kecamatan Marpoyan Damai Kota Pekanbaru 2017 not optimal yet. The factors that hamper the quality of health service still lack of human resources and the lack of facilities. Key Words : health service , health facilities, service quality